The relationship between corporate governance disclosures and balance sheet ratios / Sharifah Norhafiza Syed Ibrahim, Halizah Md Arif, Halil Paino - Syed Ibrahim, Sharifah Norhafiza; Md Arif, Halizah; Paino, Halil (Universiti Teknologi MARA Cawangan Pahang, 2007)
One of the major issues raised during the financial crisis in 1997-1998 was corporate governance practice. As a result, corporate governance reforms were then instituted and efforts were made to improve the corporate governance practices by the corporate sector. In the year 2000, The Malaysian Code of Corporate Governance was launched with a view to promote better disclosure and transparency, board effectiveness and independence and shareholder rights and activism. This paper attempts to discuss relationships between corporate governance disclosures and key balance sheet ratios among Malaysian listed companies.